2014
DOI: 10.1111/jam.12654
|View full text |Cite
|
Sign up to set email alerts
|

The influence of stabilizers and rates of freezing on preserving of structurally different animal viruses during lyophilization and subsequent storage

Abstract: This study contributes to the establishment of general guidelines for animal virus lyophilization, with particular respect to differences in virus structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 25 publications
(70 reference statements)
0
25
0
Order By: Relevance
“…It has previously been employed as a surrogate for SARS-CoV (Casanova et al 2009 ; Goyal et al 2014 ). In general, members of the same virus family are inactivated similarly under the same physical and chemical stresses (Malenovska 2014 ), although some differences even between closely related viruses may exist. Nevertheless, Alphacoronavirus 1 and SARS-CoV have been shown to have similar persistence on surfaces (Fiorillo et al 2020 ; Kampf et al 2020 ) and surface stability of SARS-CoV is markedly similar to SARS-CoV-2 (van Doremalen et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been employed as a surrogate for SARS-CoV (Casanova et al 2009 ; Goyal et al 2014 ). In general, members of the same virus family are inactivated similarly under the same physical and chemical stresses (Malenovska 2014 ), although some differences even between closely related viruses may exist. Nevertheless, Alphacoronavirus 1 and SARS-CoV have been shown to have similar persistence on surfaces (Fiorillo et al 2020 ; Kampf et al 2020 ) and surface stability of SARS-CoV is markedly similar to SARS-CoV-2 (van Doremalen et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, excipients used for lyophilization are one of the important criteria for effective phage lyophilization and also for their viability 13,14 . Earlier studies showed the use of skimmed milk, gelatin, peptone, sodium glutamate, polyethylene glycol, glycerol and other sugars (mannitol, sucrose, and trehalose) as effective excipients for phage lyophilization 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Combinations of 10% sucrose and 5% lactalbumin and 10% sucrose and 1% gelatin have shown protective effects by the reduction of titre (Ferris et al ). However, sucrose or other stabilizers have been reported to not exert any protective effect on the infectivity of picornaviruses in the process of freezing and drying, and the titres of picornaviruses were found to be markedly decreased (by 2–4·2 log 10 ) during lyophilization, according to previous studies (Fellowes ; Malenovska ). Therefore, in the current study, we tested multiple stabilizer candidates for the storage of virus seed stock for FMD vaccine without lyophilization and identified the effect of 3% sucrose on the same.…”
Section: Discussionmentioning
confidence: 70%